Convergence from the periphery: developments in Peruvian media industry and the effects on the production markets - Villanueva, Eduardo (2016)
As a mid-sized economy with a sparse tradition of film and television production, Peru offers an interesting case to study media convergence, from an industrial as well as a digital perspective. Tracking the developments requires establishing a model for convergence that is appropriate for the specifics of a country like Peru, together with data collection considering a diverse and dispersed set of production houses working mostly for local distribution and consumption. This paper will analyze the patterns emerging and relate them to the discussion on convergence and developing media industries.